Nericell: Rich Monitoring of Road and Traffic Conditions using Mobile Smartphones - Mohan, Prashanth; Padmanabhan, Venkat; Ramjee, Ramachandran (ACM Sensys, 2008)
We consider the problem of monitoring road and traﬃc conditions in a city. Prior work in this area has required the deployment of dedicated sensors on vehicles and/or on the roadside, or the tracking of mobile phones by service providers. Furthermore, prior work has largely focused on the developed world, with its relatively simple traﬃc ﬂow patterns. In fact, traﬃc ﬂow in cities of the developing regions, which comprise much of the world, tends to be much more complex owing to varied road conditions (e.g., potholed roads), chaotic traﬃc (e.g., a lot of braking and honking), and a heterogeneous mix of vehicles (2-wheelers, 3-wheelers, cars, buses, etc.). To monitor road and traﬃc conditions in such a setting, we present Nericell, a system that performs rich sensing by piggybacking on smartphones that users carry with them in normal course. In this paper, we focus speciﬁcally on the sensing component, which uses the accelerometer, microphone, GSM radio, and/or GPS sensors in these phones to detect potholes, bumps, braking, and honking. Nericell addresses several challenges including virtually reorienting the accelerometer on a phone that is at an arbitrary orientation, and performing honk detection and localization in an energy eﬃcient manner. We also touch upon the idea of triggered sensing, where dissimilar sensors are used in tandem to conserve energy. We evaluate the eﬀectiveness of the sensing functions in Nericell based on experiments conducted on the roads of Bangalore, with promising results.
Raleigh, NC, USA